APLIKASI SECURE-MESSAGE DENGAN ALGORITMA RC6 (RIVEST CODE 6) BERBASIS ANDROID - Arif Susanto Adhy; Fatsyahrina Fitriastuti; Jemmy Edwin Bororing (Universitas Janabadra, 2019)
Many factors must be considered in terms of security when communicating using information technology. SMS is one of the features that are embedded in a mobile phone is no exception in android phone. SMS is still widely used for the exchange of information, many users inadvertently share information that is privacy by sending a message by SMS. Messages that are done with SMS will be received by the provider of the service provider, then after it was forwarded to the recipient therefore sending a message by SMS need to be protected, so that the safety messages are kept strictly confidential. In this study, the software will be built in order to improve the security of messages via SMS. The application will be built to encrypt a message that will be sent and decrypt incoming messages via SMS. Applications built using the RC6 algorithm. RC6 algorithm is an algorithm flow block (block cipher) were included into the type of symmetric key cryptography system. RC6 algorithm implementation is built using Android technology, to protect and maintain the confidentiality of messages. The results of trials that have been done with this application, encrypts messages sent and can decrypt a message that was well received, the message can only be decrypted if entered the correct key corresponding to the message encryption key at the time. This application can only perform encryption and decryption of text messages (letters, numbers, symbols), to encrypt the decrypted form of the image file can not be done with this application. Keyword : SMS, Android, Cryptography, Algorithms RC6.